Numerical study on operating characteristics of direct-fired ejector air source heat pump. (25th February 2022) - Zhang, Chenghu; Huang, Xinpeng; Huang, Haicheng; Yang, Yujie
Highlights: A novel parallel system combined organic Rankine cycle and ejector heat pump cycle is proposed. Energy analysis and exergy analysis of this system are carried out. The system owns a good heat recovery rate, a flexible setting and single pure working fluid. The components with the greatest exergy destruction are the generator and the ejector heat pump. Abstract: Of the absorption heat transformer that useful to solve the problem of low-temperature heat utilization, the ejector heat pump is a good candidate because of its simple structure, flexible setting and single pure working fluid. This study aims to characterize the behavior of a novel design which replaces the traditional compression heat pump cycle with an ejector heat pump cycle and adds a waste heat recovery system to recover the heat in the flue gas. The evaluation approach takes into consideration four indices (the heating capacity per unit area of the system qh, gas consumption per unit heating capacity EC, gas heat utilization rate GUR and comprehensive heating coefficient R). The results show that the performance of this new designed system is good enough. Moreover, the influence of air and circulating water parameters on the performance of the system is studied, and it is pointed out that air parameters are the most important factors affecting the performance of direct-fired ejector air source heat pump.